African perspective on integrated space and air traffic management - Gairiseb, Alexander (Department of Electrical Engineering, 2020)
Space Traffic Management (STM) is an emerging area of interest in the space sector because States and private actors are collaborating on ways to manage the growing congestion in orbit and to mitigate the impact of space debris and space weather as part of sustainable use and exploration of outer space. Further, the pace at which commercial space operations is mushrooming and the potential for growth that the suborbital space flight market presents has led to talks about integrating space and air traffic management, through technological interfaces and harmonised regulatory regimes. But, the current global challenge is the lack of a legal framework, either in the existing space-related treaties or the adoption of a new treaty regulating STM similar to the other traffic regimes, namely aviation and maritime, and advancement in technology to seamlessly integrate Space Traffic Management (STM) and Air Traffic Management (ATM). Therefore, the proposed integration of space and air traffic management necessitates an analysis of African perspectives when it comes to consolidating the two traffic regimes, taking into account the fact that ATM in Africa is fragmented. Hence, this study analyses the legal aspects of integrating Space and Air Traffic Management from the African perspective.